Ni2P / MoNiP2 / MoP heterostructure electrocatalyst for efficient hydrogen evolution reaction

The Ni2P/MoNiP2/MoP ternary crystallization/amorphous heterostructure electrocatalyst prepared by H2-assisted synthesis method solves the problems of insufficient catalytic activity and instability of existing electrocatalysts, and achieves efficient and stable alkaline hydrogen evolution reaction performance .

CN119491254APending Publication Date: 2025-02-21CITY UNIVERSITY OF HONG KONG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311534990.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-14
Filing Date
2023-11-17
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The catalytic activity of existing transition metal-based electrocatalysts in alkaline hydrogen evolution reactions is insufficient and unstable, which limits their application in electrochemical water decomposition.

Method used

The H2-assisted synthesis method was used to prepare a ternary crystalline/amorphous heterostructure containing Ni2P, MoNiP2 and MoP, and the content of the MoNiP2 phase and the crystallinity of the MoP phase were adjusted by controlling the H2 concentration.

Benefits of technology

Achieved significantly excellent alkaline hydrogen evolution reaction performance, providing overpotentials of 20mV and 76mV to achieve current density of 10mA cm-2 and 100mA cm-2, Tafel slope is 30.6mV dec-1, and remains excellent for 100 hours of operation stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119491254A_ABST
    Figure CN119491254A_ABST
Patent Text Reader

Abstract

A ternary heterostructure comprising Ni2P, MoNiP2 and MoP wherein the ternary heterostructure comprises a crystalline region and an amorphous region, which can be used as an electrocatalyst for alkaline hydrogen evolution reactions; a cathode and an electrochemical cell comprising the cathode; as well as a preparation method and use thereof.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to ternary heterostructures comprising Ni2P, MoNiP2, and MoP, which can be used as electrocatalysts for alkaline hydrogen evolution reaction. Background Art

[0002] The electrochemical hydrogen evolution reaction (HER) is one of the most attractive approaches to achieve clean high-power-density energy and has attracted great research interest in recent years. So far, noble metal-based electrocatalysts have been used as state-of-the-art HER catalysts due to their excellent catalytic performance; however, their scarcity and operational instability fundamentally limit their widespread practical applications. To address these challenges, different transition metal-based oxides, sulfides, phosphides, and selenides have been developed and considered as alternative electrocatalysts for water electrolysis. One limitation is that their catalytic activity is still insufficient and not as competitive as their noble metal-based counterparts.

[0003] Among many recent advances, phase engineering of crystalline / amorphous heterostructured nanomaterials has revealed the effectiveness of manipulating the ratios of different phases to improve their electrochemical properties. Specifically, since HER is a two-electron transfer process involving hydrogen intermediates (H ads ) on the catalyst surface, so the catalytic performance depends largely on the free energy of hydrogen adsorption (ΔG H ). For crystalline / amorphous heterostructured nanomaterials, chemically inhomogeneous composition and saturated bonds on the surface may lead to ΔG H The phase engineering of Pd-based crystalline / amorphous heterostructure nanosheets was prepared by wet chemical methods, and their characterization results showed that they had excellent performance in ethanol oxidation reaction, because the coexistence of crystalline and amorphous structures promoted the formation of low-coordinated atoms and led to changes in the electronic band structure of Pd atoms. In addition, these wet chemical methods can also be used to construct ultrathin amorphous / crystalline Rh and bimetallic RhCu alloy nanosheets (NSs). These heterophases and alloying of Cu are beneficial to the electronic structure modulation of Rh active sites, resulting in a selectivity of indole exceeding 99.9% with high activity. Unfortunately, the synthesis of transition metal-based crystalline / amorphous heterostructures is less explored, because the redox potential of transition metal ions is significantly lower than that of noble metal ions. Although there are few studies on phase engineering of crystalline / amorphous heterostructure nanomaterials in the literature, it is highly desirable but challenging to deeply study the impact of this specific phase engineering (i.e., surface chemical inhomogeneity modulation) on the HER process. Summary of the invention

[0004] This paper provides a simple H2-assisted synthesis method for preparing crystalline / amorphous ternary Ni2P / MoNiP2 / MoP heterostructures, as well as their products and methods of use. Physical characterization results show that the content of the MoNiP2 phase and the crystallinity of the MoP phase can be adjusted by simply controlling the H2 concentration. The resulting electrocatalysts exhibit significantly superior alkaline HER performance, providing overpotentials of 20 mV and 76 mV, respectively, to achieve 10 mA cm -2 and 100mA cm -2 The current density is 30.6 mVdec. -1 . Moreover, the electrocatalyst exhibits excellent stability under constant 100 h operation, which is higher than most previously reported counterparts. We experimentally demonstrate that this superior performance can be attributed to the optimized hydrogen binding energy and favorable hydrogen adsorption / desorption kinetics. This work not only reveals the potential application of catalysts based on ternary Ni2P / MoNiP2 / MoP crystalline / amorphous heterostructure nanowires in large-scale electrochemical water splitting, but also demonstrates the importance of phase engineering in the rational design and synthesis of heterostructured electrocatalysts.

[0005] In a first aspect, provided herein is a ternary heterostructure comprising Ni2P, MoNiP2, and MoP, wherein the ternary heterostructure comprises a crystalline region and an amorphous region.

[0006] In certain embodiments, the ternary heterostructure has a crystallinity of 30% to 95%.

[0007] In certain embodiments, Ni2P nanoparticles, MoNiP2 nanoparticles, and MoP nanoparticles are disposed on at least one surface of the ternary heterostructure.

[0008] In certain embodiments, a ternary heterostructure includes a plurality of nanowires.

[0009] In certain embodiments, the plurality of nanowires have an average diameter of 25 nm to 200 nm.

[0010] In certain embodiments, when subjected to 10 mA cm-1 at 25 °C in an electrolyte comprising 1 M KOH, -2 When used as an electrocatalyst for hydrogen evolution reaction at a current density of 20 mV to 53 mV, the ternary heterostructure has an overpotential of 20 mV to 53 mV.

[0011] In certain embodiments, the ternary heterostructure comprises a plurality of nanowires having an average diameter of 25 nm to 200 nm; Ni2P nanoparticles, MoNiP2 nanoparticles, and MoP nanoparticles are arranged on at least one surface of each of the plurality of nanowires; and the crystallinity of the ternary heterostructure is 40% to 75%.

[0012] In certain embodiments, when at 25°C at 10 mA cm -2 When used as an electrocatalyst for hydrogen evolution reaction at a current density of 20 mV to 53 mV, the ternary heterostructure has an overpotential of 20 mV to 53 mV.

[0013] In certain embodiments, the ternary heterostructure has a crystallinity of 40% to 50%; and when heated to 10 mA cm at 25° C. in an electrolyte comprising 1 M KOH, -2 When used as an electrocatalyst for hydrogen evolution reaction at a current density of 20 mV to 30 mV, the ternary heterostructure has an overpotential of 20 mV to 30 mV.

[0014] In a second aspect, provided herein is an electrode comprising the ternary heterostructure described herein.

[0015] In a third aspect, provided herein is an electrochemical cell comprising an electrode as described herein, a counter electrode, an optional reference electrode, and an electrolyte solution comprising water and hydroxide ions.

[0016] In a fourth aspect, provided herein is a method of producing hydrogen gas, the method comprising applying an electric current between an electrode described herein and a counter electrode, resulting in the electrolytic reduction of water and the formation of hydrogen gas.

[0017] In a fifth aspect, provided herein is a method for preparing the ternary heterostructure described herein, the method comprising: contacting NiMoO4 with an atmosphere comprising PH3, H2 and optionally an inert gas, thereby forming a ternary heterostructure.

[0018] In certain embodiments, the step of contacting NiMoO4 with an atmosphere comprising PH3, H2, and optionally an inert gas is performed at a temperature of 400°C to 700°C.

[0019] In certain embodiments, the method further comprises the step of heating NaH2PO2 to produce PH3.

[0020] In certain embodiments, NaH2PO2 is heated at a temperature of 400°C to 700°C.

[0021] In certain embodiments, NiMoO4 is supported on a nickel foam substrate.

[0022] In certain embodiments, NiMoO4 is contacted with H2 at a concentration of 2.5% to 10% (v / v) in an inert gas.

[0023] In certain embodiments, the ternary heterostructure has a crystallinity of 40% to 50%.

[0024] In certain embodiments, the method comprises: contacting NiMoO4 with an atmosphere comprising PH3, H2 and argon at a temperature of 450°C to 550°C, wherein NiMoO4 is supported on a nickel foam substrate; contacting NiMoO4 with H2 at a concentration of 2.5% to 5% (volume / volume) in argon to form a ternary heterostructure, wherein the ternary heterostructure comprises a plurality of nanowires having an average diameter of 25nm to 100nm, wherein Ni2P nanoparticles, MoNiP2 nanoparticles and MoP nanoparticles are arranged on at least one surface of each of the plurality of nanowires, wherein the crystallinity of the ternary heterostructure is 40% to 50%. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The above and other objects and features of the present disclosure will become apparent from the following description of the present disclosure in conjunction with the accompanying drawings.

[0026] Figure 1 Physical characterization. (a) SEM image, (b) TEM image, (c) HRTEM image and corresponding (d) SAED image of NMP-10 sample; (eh) High-angle annular dark field (HAADF) STEM images and corresponding elemental maps of Ni, Mo and P of NMP-10 catalyst, respectively; the scale bar in (e) is 200 nm.

[0027] Figure 2 Structural evolution process. (a) SEM image, (b) TEM image, (c) HRTEM image and corresponding (d) SAED image of NMP-0 sample; (e) SEM image, (f) TEM image, (g) HRTEM image and corresponding (h) SAED image of NMP-5 sample; (i) SEM image, (j) TEM image, (k) HRTEM image and corresponding (l) SAED image of NMP-20 sample; (M) Total area ratio of crystalline region; (N) XRD patterns of the four prepared samples.

[0028] Figure 3 Surface electronic structure analysis. XPS spectra of (A) Ni 2p, (B) Mo 3d, and (C) P 2p of four samples, respectively; (D) calculated PM bonding ratio, (E) Ni / Mo ratio obtained from XPS and ICP results; (F) schematic diagram of the structural evolution diagram of the prepared electrocatalyst.

[0029] Figure 4 Electrochemical performance of the prepared HER electrocatalyst in 1 M KOH. (A) Polarization curve with iR compensation; (B) Current density of 10 mA cm -2 and 100mAcm -2(C) Their corresponding Tafel plots; (D) EIS spectra of the prepared samples, (E) current density difference and (F) ECSA normalized current density plotted against scan rate at −0.55 V (vs. Ag / AgCl); (G) Comparison of the NMP-10 catalyst with the recently reported active HER electrocatalysts at 10 mA cm -2 Comparison of overpotential and Tafel slope when ; (H) Stability test of NMP-10 catalyst.

[0030] Figure 5 Mechanism analysis. (A) UPS spectra and (B) CV curves recorded from 0 V to 0.5 V (vs. RHE) of the prepared catalyst. (C) The performance of the catalyst during the HER process in 1 M KOH. (D) EIS-derived Tafel plot of the catalyst obtained from the hydrogen adsorption resistance R2.

[0031] Figure 6 Depicted are the (a) XRD pattern and (b) SEM image of NiMoO4.

[0032] Figure 7 Depicted are (a) TEM image and (b) HRTEM image of NiMoO4.

[0033] Figure 8 CV curves recorded in the range of −0.6 V to −0.5 V (vs. Ag / AgCl) for (A) NMP-0, (B) NMP-5, (C) NMP-10, and (D) NMP-20, respectively, are depicted.

[0034] Fig. 9 Nyquist plots of (A) NMP-0, (B) NMP-5, (C) NMP-10, and (D) NMP-20 at various HER overpotentials in 1 M KOH are depicted. The scattered symbols represent experimental results, and the solid lines represent the fitting results of the simulation.

[0035] Fig.10 Depicted is Table 1 showing the peak intensities collected in the P 2p XPS spectra using the XPS peak software.

[0036] Fig.11 Table 2 is depicted, which shows the fitting parameters of the EIS data of NMP-0, NMP-5, NMP-10, and NMP-20, respectively. DETAILED DESCRIPTION

[0037] Throughout this disclosure, unless the context requires otherwise, the word "comprise" or variations such as "include" or "comprising" will be understood to include the stated integer or group of integers but not to exclude any other integer or group of integers. It should also be noted that in this disclosure, especially in the claims and / or paragraphs, terms such as "comprise", "include", "comprising", etc. may have the meanings given in patent law; for example, they may mean "include", "include", "contain", etc.; and terms such as "consisting essentially of" and "consisting mainly of" have the meanings given in patent law, for example, they allow elements not explicitly listed but exclude elements found in the prior art or affecting the basic or novel characteristics of the invention.

[0038] Furthermore, throughout the description and claims of the present disclosure, unless the context requires otherwise, the word "comprise" or variations such as "comprising" or "containing", will be understood to imply the inclusion of a stated integer or group of integers but not the exclusion of any other integer or group of integers.

[0039] Unless otherwise specifically stated, the use of the singular herein includes the plural (and vice versa). In addition, when the term "about" is used before a quantitative value, the present teachings also include the specific quantitative value itself unless otherwise specifically stated. As used herein, the term "about" refers to a variation of ±10%, ±7%, ±5%, ±3%, ±1%, or ±0% of the nominal value, unless otherwise stated or inferred.

[0040] Provided herein is a ternary heterostructure comprising Ni2P, MoNiP2 and MoP, wherein the ternary heterostructure comprises a crystalline region and an amorphous region. In certain embodiments, the ternary heterostructure is disposed on a nickel foam substrate.

[0041] The surface of the ternary heterostructure may have a dominant crystalline structure. In certain embodiments, the crystalline region of the ternary heterostructure may account for 30% to 95%, 35% to 95%, 40% to 95%, 45% to 95%, 50% to 95%, 55% to 95%, 60% to 95%, 60% to 90%, 60% to 85%, 60% to 80%, 65% to 80%, 70% to 80%, 70% to 75%, 70% to 95%, or 74.26% to 96.34% of the surface area of ​​the ternary heterostructure. In certain embodiments, the crystallinity of the ternary heterostructure is about 74.26% based on the surface area of ​​the ternary heterojunction.

[0042] Ni2P nanoparticles, MoNiP2 nanoparticles and MoP nanoparticles can be arranged on at least one surface of the ternary heterostructure. In certain embodiments, the average lateral size of the MoNiP2 nanoparticles and the MoP nanoparticles is 2nm to 40nm, 10nm to 40nm, 20nm to 40nm or 20nm to 30nm. In certain embodiments, the average lateral size of the MoNiP2 nanoparticles and the MoP nanoparticles is about 26nm.

[0043] like Figure 2 As shown, the ternary heterostructure may include multiple nanowires. The average diameter of multiple nanowires generally depends on the reaction conditions for preparing the ternary heterostructure, and is in the range of 25nm to 200nm, 25nm to 175nm, 25nm to 150nm, 25nm to 125nm, 25nm to 100nm, 25nm to 75nm, 25nm to 50nm, 50nm to 100nm, 50nm to 200nm, 75nm to 200nm, 100nm to 200nm, 100nm to 150nm, 125nm to 200nm, 150nm to 200nm, 175nm to 200nm, 50nm to 175nm, 75nm to 150nm or 100nm to 125nm. In certain embodiments, the average diameter of multiple nanowires is about 50nm, about 100nm or about 150nm.

[0044] The ternary heterostructure can be prepared by the following method, comprising: contacting NiMoO4 with an atmosphere comprising PH3, H2 and optionally an inert gas, thereby forming the ternary heterostructure. In certain embodiments, NiMoO4 is disposed on a nickel foam substrate.

[0045] An atmosphere comprising PH3, H2, and an optional inert gas may react with NiMoO4 at a temperature of 400°C or higher. In certain embodiments, an atmosphere comprising PH3, H2, and an optional inert gas reacts with NiMoO4 at a temperature of 400°C to 1,000°C, 400°C to 900°C, 400°C to 800°C, 400°C to 700°C, 400°C to 600°C, 450°C to 600°C, 450°C to 550°C, or 475°C to 525°C. In certain embodiments, an atmosphere comprising PH3, H2, and an optional inert gas reacts with NiMoO4 at about 500°C.

[0046] PH3 used in the methods described herein is commercially available or can be prepared using any method known in the art. In certain embodiments, PH3 is prepared in situ by thermal decomposition of NaH2PO2 or a hydrate thereof (e.g., NaH2PO2•H2O) in the presence of NiMoO4. In certain embodiments, NaH2PO2 or a hydrate thereof is heated at a temperature of 400°C or higher. In certain embodiments, NaH2PO2 or a hydrate thereof is heated at a temperature of 400°C to 1000°C, 400°C to 900°C, 400°C to 800°C, 400°C to 700°C, 400°C to 600°C, 450°C to 600°C, 450°C to 550°C, or 475°C to 525°C. In certain embodiments, NaH2PO2 or a hydrate thereof is heated at a temperature of about 400°C. The temperature of the reaction can be increased at a rate of 1°C / minute to 10°C / minute, 1°C / minute to 9°C / minute, 1°C / minute to 8°C / minute, 1°C / minute to 7°C / minute, 1°C / minute to 6°C / minute, 1°C / minute to 5°C / minute, 1°C / minute to 4°C / minute, 1°C / minute to 3°C / minute, or 2°C / minute to 3°C / minute.

[0047] The inert gas can be helium, nitrogen, argon, neon, and mixtures thereof. In certain embodiments, the inert gas is argon.

[0048] In embodiments where an inert gas is present, the atmosphere may comprise 2% to 20% v / v, 2% to 19% v / v, 2% to 18% v / v, 2% to 17% v / v, 2% to 16% v / v, 2% to 15% v / v, 2% to 14% v / v, 2% to 13% v / v, 2% to 12% v / v, 2% to 11% v / v, 2% to 12% v / v, 2% to 13% v / v, 2% to 14% v / v, 2% to 15% v / v, 2% to 16% v / v, 2% to 17% v / v, 2% to 18% v / v, 2% to 19% v / v, 2% to 20% v / v, 2% to 21% v / v, 2% to 22% v / v, 2% to 23% v / v, 2% to 24% v / v, 2% to 25% v / v, 2% to 26% v / v, 2% to 27% v / v, 2% to 28% v / v, 2% to 29% v / v, 3% to 30% v / v, 3% to 31% v / v, 3% to 32% v / v, 3% to 33% v / v, 3% to 34% v / v, 3% to 35% v / v, 3% to 36% v / v, 3% to 37% v / v, 3% to 38% v / v In some embodiments, the atmosphere comprises H at a concentration of about 10% v / v in an inert gas.

[0049] Then, the samples were treated at 500°C for 2 hours in an Ar / H2 atmosphere with a heating rate of 2.5°C / min, and the flow rates were adjusted to 200 / 0 sccm, 195 / 5 sccm, 190 / 10 sccm, and 180 / 20 sccm.

[0050] The atmosphere comprising H2 and an optional inert gas may be contacted with NaH2PO2 at a rate of 10 sccm to 300 sccm, 50 sccm to 300 sccm, 100 sccm to 300 sccm, 150 sccm to 300 sccm, 150 sccm to 250 sccm, or 175 sccm to 225 sccm. In certain embodiments, the atmosphere comprising H2 and an optional inert gas may be contacted with NaH2PO2 at a rate of about 200 sccm.

[0051] The NiMoO4 may be contacted with H2 at a rate of 1 to 50, 1 to 45, 1 to 40, 1 to 35, 1 to 30, 1 to 25, 1 to 20, 5 to 20, 5 to 15, 6 to 14, 7 to 13, 8 to 12, or 9 to 11 standard cubic centimeters per minute (sccm). In certain embodiments, the NiMoO4 is contacted with H2 and an inert gas at a rate of 5-50 sccm.

[0052] An atmosphere comprising H 2 and an inert gas may be contacted with NaH 2 PO 2 at a rate of 200 seem, with the H 2 concentration being 2.5% to 10% v / v, 2.5% to 7.5% v / v, 2.5% to 5% v / v, or 5% to 10% v / v.

[0053] The present disclosure also provides an electrode comprising the ternary heterostructure described herein.

[0054] The present disclosure also provides an electrochemical cell comprising two or more electrodes, wherein the two or more electrodes may include an electrode comprising a ternary heterostructure described herein, a counter electrode (or counter electrode / reference electrode), an optional reference electrode (e.g., in a three-electrode system), and an electrolyte solution comprising hydroxide ions (the electrolyte solution being between and in contact with the electrode, the counter electrode, and the optional reference electrode).

[0055] Counter electrode refers to an electrode paired with a working electrode, and the current passing through the counter electrode is equal to the current passing through the working electrode and has an opposite sign. The counter electrode can include a counter electrode (i.e., counter electrode / reference electrode) that can also be used as a reference electrode. Any suitable counter electrode known in the art can be used herein. For example, the counter electrode can include carbon (e.g., highly oriented pyrolytic graphite), metal (e.g., platinum), alloy (e.g., stainless steel), glassy carbon, conductive polymers, etc.

[0056] The reference electrode can be selected from a standard hydrogen electrode, a calomel electrode, a copper-copper (II) sulfate electrode, a silver chloride electrode, a palladium-hydrogen electrode, a mercury-mercurous sulfate electrode, and the like.

[0057] The electrolyte solution may include a hydroxide derived from a hydroxide source selected from the group consisting of LiOH, NaOH, KOH, CsOH, Mg(OH)2, Ca(OH)2, Sr(OH)2, and mixtures thereof.

[0058] The concentration of hydroxide ions in the electrolyte solution may be in the range of 0.1 M to 10 M, 0.1 M to 9 M, 0.1 M to 8 M, 0.1 M to 7 M, 0.1 M to 6 M, 0.1 M to 5 M, 0.1 M to 4 M, 0.1 M to 3 M, 0.1 M to 2 M, 0.5 M to 1.5 M, or 0.75 M to 1.25 M. In certain embodiments, the concentration of hydroxide ions in the electrolyte solution is about 1 M.

[0059] The present disclosure also provides a method of producing hydrogen, the method comprising applying an electric current between an electrode comprising the ternary heterostructure described herein and a counter electrode, resulting in electrolytic reduction of water and formation of hydrogen.

[0060] When the electrolyte contains 1M KOH at 25°C and 10mAcm -2 When used as an electrocatalyst for hydrogen evolution reaction at a current density of 1000 Å, the overpotential of the ternary heterostructure can be 20 mV to 85 mV, 20 mV to 67 mV, 20 mV to 53 mV, 20 mV to 50 mV, 20 mV to 45 mV, 20 mV to 40 mV, 20 mV to 35 mV, 20 mV to 30 mV, or 20 mV to 25 mV. In certain embodiments, when the overpotential is 10 mA cm-1 at 25 ° C in an electrolyte comprising 1 M KOH, the overpotential is 20 mV to 85 mV, 20 mV to 67 mV, 20 mV to 53 mV, 20 mV to 50 mV, 20 mV to 45 mV, 20 mV to 40 mV, 20 mV to 35 mV, 20 mV to 30 mV, or 20 mV to 25 mV. -2 When used as an electrocatalyst for hydrogen evolution reaction at a current density of , the overpotential of the ternary heterostructure is about 20 mV.

[0061] The Ni2P / MoNiP2 / MoP ternary heterostructure was prepared by phosphorylating NiMoO4 nanowires with NaH2PO2 at 500°C in a mixed atmosphere of Ar / H2 (190:10, v / v, represented by NMP-10). The morphology of NMP-10 was first observed using a scanning electron microscope (SEM). It was found that the nickel foam substrate was completely covered with twisted nanowires ( Figure 1 a). Transmission electron microscopy (TEM) image showing many protruding crystalline nanoparticles (marked with dotted circles) attached to the nanowire skeleton ( Figure 1 b) This observation suggests that the phosphating process may induce the separation of Ni and Mo elements from the bimetallic oxide precursors, which is consistent with previous reports. Figure 1In the high-resolution TEM (HRTEM) image shown in c, the lattice spacings of 0.22 nm, 0.21 nm, and 0.28 nm are attributed to the (111) plane of Ni2P (JCPDS NO.74-1385), the (101) plane of MoP (JCPDS NO.65-6489), and the (100) plane of MoNiP2 (JPDS NO.65-1985), respectively. At the same time, abundant crystalline / amorphous interfaces (amorphous regions marked with A) were observed on the catalyst surface. Correspondingly, the polycrystalline rings shown in the selected area electron diffraction (SEAD) can be pointed to the (220) and (300) planes of Ni2P, the (100) and (103) planes of MoNiP2, and the (101) and (201) planes of MoP ( Figure 1 d), which further proves the successful preparation of Ni2P / MoNiP2 / MoP ternary heterostructure. Elemental mapping shows that in NMP-10 nanowires, P and Mo elements are uniformly distributed, while Ni element is enriched in certain areas ( Figure 1 eh), which indicates that a clear phase separation occurred during the preparation process.

[0062] To further demonstrate the precise control of crystalline / amorphous phase engineering, a series of samples were carefully fabricated by optimizing the H2 concentration. Ni2P / MoP was also prepared without the introduction of H2 (denoted by NMP-0) for comparison. The morphology of NMP-0 was first observed by SEM ( Figure 2 a). In contrast to the SEM image of pristine NiMoO4 nanowires ( Figure 6 ), almost no morphological changes were observed after phosphorylation. In addition, the nanowires with a typical diameter of about 150 nm were vertically aligned and completely covered the surface of the nickel foam substrate. As shown in the TEM image ( Figure 2 b), some crystalline nanoparticles (marked by dotted circles) are attached to the nanowire skeleton, which is different from the smooth surface of NiMoO4 ( Figure 7 ). The obvious phase separation phenomenon observed on the NMP-0 surface is due to the transformation of NiMoO4 into Ni-MoO2 heterostructure (Ni nanoparticles anchored on the MoO2 skeleton) at high temperature. At the same time, it is phosphorylated to Ni2P / MoP due to the reaction with PH3. HRTEM images show the close contact between Ni2P and MoP. The lattice fringes of 0.30nm, 0.17nm and 0.21nm fully point to the (110) plane of Ni2P, the (110) and (101) planes of MoP, respectively ( Figure 2 c). In addition, SEAD can be directed to the (111), (210), and (300) planes of Ni2P and the (101) plane of MoP ( Figure 2d). After the introduction of H2 (Ar:H2=195:5, v / v, expressed as NMP-5), the nanowires became curved and their diameters decreased (about 87 nm, Figure 2 e). At the same time, TEM images show a significant increase in the density of giant highly crystalline nanoparticles on the amorphous backbone ( Figure 2 f). Surprisingly, a new phase of NiMoP2 was observed in the HRTEM and SEAD results, where the 0.28 nm lattice fringe space is attributed to the (100) plane of NiMoP2 ( Figure 2 g and 2h). However, when the hydrogen flow rate was increased to 20 SCCM (denoted as NMP-20), the nanowires aggregated and the diameter increased slightly according to the statistical results (about 68 nm, Figure 2 i). TEM images show that the nanowire skeleton is almost completely covered by a highly crystalline surface, with only small areas showing amorphous features ( Figure 2 j, marked by a dotted circle). HRTEM images and SEAD results show that all Ni2P, MoNiP2, and MoP have high crystalline characteristics, and clear grain boundaries are observed ( Figure 2 k and 2l). The mass contents of NMP-20, NMP-10, NMP-5 and NMP-0 were determined as follows: for NMP-20, MoNiP2:MoP:Ni2P was 49.1:29.1:21.8; for NMP-10, MoNiP2:MoP:Ni2P was 17.7:13.8:68.5; for NMP-5, MoNiP2:MoP:Ni2P was 1.4:2.6:96; for NMP-0, MoP:Ni2P=2.4:97.6. The crystalline surface areas of NMP-0, NMP-5, NMP-10 and NMP-20 were 30.62%, 46.38%, 74.26% and 96.34%, respectively. Then, the roughness ratio of the crystalline region is summarized in Figure 2 M. It is obvious that the area ratio of crystalline / amorphous regions increases with the increase of hydrogen concentration in the gas mixture, which can be attributed to the fact that the introduced hydrogen reduces the reaction barrier of MoP and Ni2P to produce NiMoP2 in PH3 atmosphere, and the content of NiMoP2 depends on the hydrogen concentration. In addition, this hydrogen concentration-dependent NiMoP2 plays a decisive role in the crystalline / amorphous ratio. The above characterization results show that the H2 / PH3 mixture significantly affects the surface chemical inhomogeneity. More phase and crystal structure information can be obtained in the X-ray diffraction (XRD) pattern ( Figure 2N). In the NMP-0 sample, the peak of MoP is weaker than the crystalline peak of Ni2P, indicating that MoP exists mainly in the form of an amorphous phase, which is consistent with the TEM results. After the introduction of hydrogen, a new phase of MoNiP2 appears in the sample, and the crystallinity of MoP is significantly improved, which further indicates the successful phase engineering in the Ni2P / MoNiP2 / MoP ternary heterostructure.

[0063] Since phase engineering significantly affects the surface electronic structure of the material, X-ray photoelectron spectroscopy (XPS) was subsequently used to study the surface chemical state and chemical composition of the obtained electrocatalyst. For the Ni-2p spectrum, the main peaks at 853.4 eV, 857.0 eV, and 861.8 eV can be attributed to the Ni-P bonding peak, the oxidized Ni 2+ / Ni 3+ Peak and satellite peak ( Figure 3A ). With the increase of hydrogen flow rate, a clear blue shift and an increase of Ni-P peak intensity were observed in the spectrum, indicating that electrons were transferred to Ni atoms in the coordination environment. In the Mo 3d spectrum, the peaks at 235.7 eV and 233.4 eV are attributed to Mo 6+ The peaks at 232.3 eV and 229.5 eV are attributed to Mo 4+ , while the Mo-P peaks are centered at 230.8eV and 227.8eV, respectively ( Figure 3B ). At the same time, with the increase of hydrogen concentration, a red shift phenomenon and an increase of Mo-P peaks were observed in the Mo3d spectrum, indicating the electron loss of Mo atoms. Regarding the P 2p spectrum of the catalyst, the increase of PM peaks at 129.3eV and 130.3eV indicates that the PM bonding ratio in the electrocatalyst is controllable, which has a strong influence on the surface electronic structure ( Figure 3C ). In particular, for NMP-20 catalyst, the surface PM bonding ratio can reach 49.42% ( Figure 3D , Fig.10 In addition, since the detection depth of XPS technology is 3nm to 10nm, and the emission spectrum results of inductively coupled plasma (ICP) can give an overall composition analysis, combining these two characterization techniques can give more detailed information about the composition of the surface and internal regions. Figure 3E As shown in Figure 2, the ICP results show that the Ni / Mo ratio of these catalysts remains almost unchanged. In contrast, the XPS results show that this value decreases continuously with the increase of the hydrogen ratio, indicating that Mo atoms migrate outward due to the reaction between MoP and Ni2P. Combined with the previous analysis, the surface structure and composition evolution of the electrocatalysts are proposed, such as Figure 3FAs shown. When only PH3 is introduced, the outward migration and phosphorylation of Ni atoms occur simultaneously, and highly crystalline Ni2P nanoparticles are formed on the surface. As for Mo atoms, only a small part of Mo atoms precipitate from the skeleton to form a crystalline MoP phase (XRD results of NMP), and most Mo atoms react with PH3 to form an amorphous MoP nanowire skeleton. Once hydrogen is introduced into the system, Mo atoms become active, resulting in improved crystallinity of MoP. More importantly, the reaction barrier between MoP and Ni2P is reduced, and a new phase MoNiP2 is formed at the interface of the MoP / Ni2P heterostructure. With the increase of hydrogen concentration, it is confirmed that the crystallinity of all phases increases and the relative MoNiP2 content increases until the catalyst surface is completely covered with a highly crystalline phase.

[0064] To elucidate the superior electrochemical properties induced by phase engineering, the electrochemical performances of the as-prepared materials were evaluated in 1.0 M KOH electrolyte. Figure 4 A shows the polarization curves of the samples. Among these electrodes, NMP-10 exhibits the best HER performance and reaches 10 mA cm -2 The overpotential of NMP-10 with the catalytic current density of 20 mV is much lower than that of NMP-5 (53 mV), NMP-20 (67 mV) and NMP-0 (85 mV). More importantly, Figure 4 As shown in B, NMP-10 only needs 76mV to reach 100mAcm -2 , indicating its excellent electrocatalytic performance. From the perspective of HER kinetics evaluated by Tafel plot, NMP-10 catalyst provided the lowest slope value of 30.6 mV dec -1 , better than NMP-5 catalyst (56.8mV dec -1 )、NMP-20 catalyst (76.1mV dec -1 ) and NMP-0 catalyst (119.8 mV dec -1 ), which means that NMP-10 catalyst has superior reaction kinetics ( Figure 4 C). In addition, the Tafel slope of NMP-10 is close to 30 mV dec. -1 , indicating that the HER kinetics process is mainly composed of the water dissociation step (M+H2O+e→MH ads +OH - , M represents the catalyst, i.e., Volmer-Tafel mechanism). In contrast, the Tafel slopes of NMP-5, NMP-20, and NMP-0 fall within 40 mV dec. -1 Up to 120mV dec -1 The rate-determining step is the combination of insufficient hydrogen intermediates (MH ads+H2O+e-→M+H2+OH - , i.e., the Volmer-Heyrovsky step). It is also noteworthy that no improvement in HER performance was observed with increasing MoNiP2 content. Thus, the improvement in HER performance must be due to the synergistic effect between multiple components, which will be discussed in detail later. In addition, electrochemical impedance spectroscopy (EIS) was employed to explore the HER kinetics at the interface between the electrode and the electrolyte, as shown in Figure 2. Figure 4 D. The recorded Nyquist plot is simulated by a double parallel equivalent circuit model, where R ct reflects the charge-transfer dynamics ( Figure 4 D), and the values ​​of 10.36Ω, 66.18Ω, 76.89Ω, and 133.70Ω for NMP-10, NMP-5, NMP-20, and NMP-0 samples indicate that the enhanced HER performance is attributed to the lower charge transfer. In addition, we further measured the electrochemical double layer capacitance (C dl ) to evaluate the electrochemical surface area of ​​the prepared catalyst ( Figure 8 ), where C dl is considered to be proportional to the effective surface area of ​​the catalyst. Figure 4 As can be seen from Figure E, the C dl The values ​​are ~12.9mF / cm 2 、8.4mF / cm 2 , 7.1mF / cm 2 and 3.4mF / cm 2 , indicating that the NMP-10 catalyst has a more active surface area. Then, normalized to the ECSA specific current density, NMP-10 shows a much higher specific current density than other catalysts in the entire measured voltage range ( Figure 4 F), indicating that the intrinsic activity of NMP-10 electrode is indeed higher than that of NMP-5, NMP-20 and NMP-0 catalysts. It is worth noting that our electrocatalysts show superior electrochemical performance in terms of overpotential and Tafel slope compared with recently reported catalysts, even for some noble metal-based catalysts ( Figure 4 G). We then investigated the stability of the catalysts under electrocatalytic operation. In particular, we investigated the stability of the catalysts under electrocatalytic operation by 2 and 500mA / cm 2 ) to measure the actual operation of the NMP-10 catalyst. Even after a long period of 100 hours, no significant decrease in electrolysis was observed, indicating the potential for using these catalysts for long periods of time in electrochemical processes.

[0065] Based on the experimental work of the system and DFT theoretical calculations, the hydrogen binding energy (HBE) can be used as a descriptor for HER performance. Therefore, to deeply explore the activity mechanism of the obtained catalysts, a correlation study between HER activity and experimentally measured HBE was constructed using ultraviolet photoelectron spectroscopy (UPS) and CV methods. First, the valence state structure of the prepared catalysts was detected using UPS. The electron bands of all samples cross the Fermi level ( Figure 5 A), indicating their metallic nature. The peaks beside the Fermi level correspond to the 3d states of metallic Ni. The positions of their binding energies are away from the Fermi level in the following order: NMP-0 < NMP-20 < NMP-5 < NMP-10. Based on the d-band theory, a downshifted d-band leads to a weakened adsorption strength. Therefore, the order of HBE is: NMP-0 > NMP-20 > NMP-5 > NMP-10. In addition, the HBE of the active sites can be obtained through ΔH = -FE 峰 associated with the potential of the H upd desorption peak (E 峰 ). Compared with NMP-5 (-0.29 eV), NMP-20 (-0.30 eV), and NMP (-0.34 eV), the HBE of NMP-10 is lower, at -0.23 eV ( Figure 5 B), which is consistent with the UPS results. In this case, the relatively weak H chemisorption strength of NMP-10 compared to other catalysts leads to an acceleration of the hydrogen desorption behavior. Then, the adsorption behavior of hydrogen on the catalyst was also studied by in-situ EIS technology because the second parallel component ( and R1) can reveal the hydrogen adsorption behavior on the catalyst surface, where R1 and reflect the hydrogen adsorption resistance and pseudo-capacitance, respectively ( Figure 4 inset of Figure 8 D, Fig.11 ). As shown in Figure 5 C, the -η curve provides information on the hydrogen adsorption charge on the catalyst surface during the HER process. The highest value of NMP-10 indicates the highest H ads coverage on the surface among the prepared samples, which is consistent with the Tafel slope analysis. In this way, the corresponding hydrogen adsorption kinetics on the electrode surface also changes. Given the potential-dependent R1 of all catalysts, it is reasonable to quantify their hydrogen adsorption kinetics by plotting log R1 versus η and calculating the Tafel slope derived from EIS according to Ohm's law. As shown in Figure 5As shown in Figure D, the EIS-derived Tafel slope of NMP-10 is significantly reduced, indicating enhanced hydrogen adsorption kinetics. Overall, the above detailed experimental results strongly demonstrate that the controllable surface chemical inhomogeneity in ternary heterostructures can optimize the HER process by accelerating the adsorption and desorption kinetics of hydrogen intermediates.

[0066] In this work, we developed a simple H2-assisted method to prepare ternary Ni2P / MoNiP2 / MoP crystalline / amorphous heterostructure nanowires on conductive substrates. Based on various characterization techniques, the content of MoNiP2 phase and the crystallinity of MoP phase can be tuned by simply controlling the H2 concentration. The optimized surface chemical inhomogeneity yields appropriate hydrogen binding energy and favorable hydrogen adsorption / desorption kinetics. As a result, the obtained electrocatalysts exhibit excellent alkaline HER performance, providing overpotentials of 20 mV and 76 mV to reach 10 mA cm -2 and 100mAcm -2 The current density is 30.6 mV dec. -1 Importantly, the catalyst exhibits excellent stability under constant 100 h operation, which is higher than most previously reported electrocatalysts. This work not only demonstrates the potential application of ternary Ni2P / MoNiP2 / MoP crystalline / amorphous heterostructure nanowire catalysts in practical large-scale electrochemical water splitting, but also demonstrates the importance of phase engineering in the rational design and synthesis of heterostructured electrocatalysts.

[0067] experiment

[0068] Preparation of Ni2P / MoNiP2 / MoP ternary heterostructure nanowires on nickel foam

[0069] In this work, all nickel foams were treated as follows: acetone treatment, hydrochloric acid (2M), deionized water treatment and ethanol treatment, respectively for 10 minutes. Typically, 0.5mmol NiCl2 and 0.5mmol Na2MoO4 were added to 15mL of deionized water and mixed thoroughly. Then, a piece of nickel foam and the homogenous solution were sealed into a polytetrafluoroethylene-lined stainless steel autoclave, which was heated at 160°C in an electric furnace for 6 hours. After hydrothermal treatment, the resulting nickel foam covered with NiMoO4 nanowires was washed several times with deionized water and ethanol under ultrasonic treatment, and then dried overnight in a vacuum oven at 80°C.

[0070] Then, NiMoO4 nanowires / nickel foam and 800 mg of NaH2PO2 were placed in two separate positions of the quartz boat, with the NaH2PO2 powder located on the upstream side of the gas. The sample was then treated at 500°C for 2 hours at a heating rate of 2.5°C / min under an Ar / H2 atmosphere, and the flow rates were adjusted to 200 / 0sccm, 195 / 5sccm, 190 / 10sccm, and 180 / 20sccm, respectively. The final product was obtained after cooling to room temperature.

[0071] Material characterization

[0072] The images were obtained by scanning electron microscopy (SEM, Phenom World, The Netherlands), field emission SEM (SU-8010, Hitachi, Tokyo, Japan), Bruker D2 phase analyzer (Bruker, Billerica, MA, USA) equipped with monochromatized Cu-Kα radiation, transmission electron microscopy (TEM), and high-resolution (HR) TEM (Tecnai G 2 The prepared samples were characterized by X-ray photoelectron spectroscopy (XPS) (VG Multilab 2000, Thermo Fisher Scientific, Waltham, MA, USA). UPS HeII spectra were obtained using a SPECS Leybold EA 11MCD hemispherical electron analyzer with an excitation energy of 40.82 eV. The binding energy scale is related to the Fermi level of the Au samples. The area and perimeter of the crystalline particles were counted using ImageJ software.

[0073] Electrochemical measurements

[0074] All electrochemical characterizations were investigated by a Gamry 300 electrochemical workstation in a conventional three-electrode cell at room temperature. The prepared sample (Ni2P / MoNiP2 / MoP ternary heterostructure nanowires on nickel foam), a saturated calomel electrode, and a carbon rod were used as working, reference, and counter electrodes, respectively. The active area of ​​the electrocatalyst immersed in the electrolyte was defined by applying silicone rubber. All calibrated potentials were relative to the reversible hydrogen electrode (RHE). The potentials were measured at 5 mV s in 1 M KOH aqueous solution (pH = 14). -1 The HER activity was studied at a scan rate of .

Claims

1. A ternary heterostructure comprising Ni2P, MoNiP2 and MoP, characterized in that: The ternary heterostructure includes a crystalline region and an amorphous region.

2. The ternary heterostructure according to claim 1, characterized in that: The crystallinity of the ternary heterostructure is 30% to 95%.

3. The ternary heterostructure according to claim 1, characterized in that: Ni2P nanoparticles, MoNiP2 nanoparticles, and MoP nanoparticles are arranged on at least one surface of the ternary heterostructure.

4. The ternary heterostructure according to claim 1, characterized in that: The ternary heterostructure includes a plurality of nanowires.

5. The ternary heterostructure according to claim 4, characterized in that: The average diameter of the plurality of nanowires is 25 nm to 200 nm.

6. The ternary heterostructure according to claim 1, characterized in that: When the electrolyte contains 1M KOH at 25 °C and 10 mA cm -2 When used as an electrocatalyst for hydrogen evolution reaction at a current density of , the overpotential of the ternary heterostructure is 20 mV to 53 mV.

7. The ternary heterostructure according to claim 1, characterized in that: The ternary heterostructure includes a plurality of nanowires having an average diameter of 25 nm to 200 nm; Ni2P nanoparticles, MoNiP2 nanoparticles and MoP nanoparticles are arranged on at least one surface of each of the plurality of nanowires; and the crystallinity of the ternary heterostructure is 40% to 75%.

8. The ternary heterostructure according to claim 7, characterized in that: At 25℃ at 10mAcm -2 When used as an electrocatalyst for hydrogen evolution reaction at a current density of , the overpotential of the ternary heterostructure is 20 mV to 53 mV.

9. The ternary heterostructure according to claim 7, characterized in that: The ternary heterostructure has a crystallinity of 40% to 50%; and when subjected to 10 mA cm-2 at 25° C. in an electrolyte comprising 1 M KOH, -2 When used as an electrocatalyst for hydrogen evolution reaction at a current density of , the overpotential of the ternary heterostructure is 20 mV to 30 mV.

10. An electrode comprising the ternary heterostructure according to claim 1.

11. An electrochemical cell comprising the electrode of claim 10, a counter electrode, an optional reference electrode, and an electrolyte solution comprising water and hydroxide ions.

12. A method of producing hydrogen, the method comprising applying an electric current between the electrode of claim 11 and a counter electrode, resulting in electrolytic reduction of water and formation of hydrogen.

13. A method for preparing the ternary heterostructure according to claim 1, the method comprising: NiMoO4 is contacted with an atmosphere comprising PH3, H2 and optionally an inert gas to form the ternary heterostructure.

14. The method according to claim 13, characterized in that The step of contacting NiMoO4 with an atmosphere comprising PH3, H2 and optionally an inert gas is carried out at a temperature of 400°C to 700°C.

15. The method according to claim 13, characterized in that The method also includes the step of heating NaH2PO2 to produce PH3.

16. The method according to claim 15, characterized in that NaH2PO2 is heated at a temperature of 400°C to 700°C.

17. The method according to claim 13, characterized in that The NiMoO4 is supported on a nickel foam substrate.

18. The method according to claim 13, characterized in that The NiMoO4 is contacted with H2 at a concentration of 2.5% to 10% (v / v) in an inert gas.

19. The method according to claim 13, characterized in that The crystallinity of the ternary heterostructure is 40% to 50%.

20. The method according to claim 13, characterized in that The method includes: contacting NiMoO4 with an atmosphere comprising PH3, H2 and argon at a temperature of 450°C to 550°C, wherein the NiMoO4 is supported on a nickel foam substrate; contacting the NiMoO4 with H2 having a concentration of 2.5% to 5% (volume / volume) in an inert gas to form the ternary heterostructure, wherein the ternary heterostructure includes a plurality of nanowires having an average diameter of 25nm to 100nm, wherein Ni2P nanoparticles, MoNiP2 nanoparticles and MoP nanoparticles are arranged on at least one surface of each of the plurality of rice wires, wherein the crystallinity of the ternary heterostructure is 40% to 50%.